My perfect wedding - Marsoli, Lisa Ann, 1958-; Disney Storybook Artists (New York : Random House, 2004)
"Planning a wedding is a big job-- but not too big for a princess as perfect as Cinderella!"--P. [4] of cover.
Keywords: Cinderella (Legendary character) -- Juvenile fiction; Princesses -- Juvenile fiction; Fairy godmothers -- Juvenile fiction; Weddings -- Planning -- Juvenile fiction